Soil Resource Mapping and Assessment of Soils at Different Physiographic Divisions in Selected Mandals of Prakasam District, Andhra Pradesh: A Remote Sensing and GIS Approach - Ram, R. L.; Sharma, P. K.; Chatterjee, T.; Kumar, Sarvajeet; Ahmed, N. (International Journal of Bio-resource and Stress Management, 2023)
A rapid reconnaissance soil survey of Markapur, Kambham, Giddalur and Komarulu mandals of Prakasam district, Andhra Pradesh was carried out in 2009-10 for soil resource mapping using a hard copy of geo-referred false colour composite image of IRS-P6, LISS-III, and Survey of India (SOI) topo-maps no. 57 I/16, 57 M/1, 57 M/2, 57 M/3, 57 M/4, 57 M/5 and 57 M/6 of 1:50,000 scale as auxiliary data set. The study area lies between 15o30’ to 16o00’ N latitudes and 78o45’ to 79o30’ E longitudes with total geographical area of 3, 52,185 ha. Alluvium, quartzite, sandstone and shale were main geologic formation. Physiographically, soils of hill side slope and undulating pediments developed over mixed geology of quartzite, sandstone and shale 1apped into 9 mapping units. Likewise, Soils of pediplains and stream bank developed over shale are light to dark coloured, deep to very deep and have fine loamy to fine texture and low fertile. These soils are mostly under rainfed cultivation in pediplains and waste land in stream bank extended over 51.2% of the total area and mapped into 7 mapping units. Based on soil limitations, soils of undulating pediments and hill side slope are grouped under land capability class VI and VII whereas soils pediplains and stream bank was under land capability class II and III respectively.